Tecnología para la reforestación en América Latina - Keyes Hennin, Michael R. (Instituto de Ecología, A.C., 2016)
Deforestation has surpased reforestation efforts throughout the tropics. There are a plethora of historical precedents for the consequences of ambitious nations with frontier style colonizing and agricultural development which has led to a reduction of forested areas. The objectives of this paper are to review the similarities between the development of conservation and restoration programs for forest soils degraded by agriculture and, above all, the technology developed to aid reforestation, emphasizing efforts in Latin America.